Aliran-Aliran Paham Keagamaan Dalam Islam Berlandaskan Moderasi Beragama - Ayun, Rati Pratama (Moderatio: Jurnal Moderasi Beragama, 2024)
The diversity of educational backgrounds, socio-cultural situations, and so on has caused the positioning of religion as a normative reference to produce disparities, both at the levels of cognition, perception, and interpretation as well as at the level of diversity of self-expression. As a result, there are individuals who think about and follow a different understanding of religion than the general public. The purpose of this research is to discover the origins of religious schools of thought in Islam. The method used in this study is a qualitative method with data collection techniques through literature studies and interviews. The findings show that ignorance of adherents of Islam and its various aspects, rapid socio-economic changes, globalization that causes disorientation, psychological dislocation within certain circles of society, and fragmentation of authority over the interpretation of the holy texts (the Qur'an) have implications for a shift in religious authority that will become a driving factor for the birth of the principles of Islamic teachings.